Rekontruksi Konsep Balanja al-Nikāḥ dalam Adat Pernikahan Masyarakat Banjar: Analisis Alasan Hukum Syaikh Muhammad Arsyad al-Banjari dalam Kitāb al-Nikāḥ - Muzainah, Gusti; Hafidzi, Anwar; al-Amruzi, M. Fahmi (Institut Agama Islam Negeri (IAIN) Pontianak, 2025)
The practice of wealth transfer beyond the obligatory mahr (dower) in customary marriage represents a complex socio-legal phenomenon, as it holds not only symbolic significance but also directly impacts gender relations, household economic responsibilities, and the perpetuation of social hierarchies. Within the Banjarese community of South Kalimantan, this practice is institutionalized through the tradition of jujuran, which involves the groom’s family transferring money and personal items to the bride before the marriage contract. Originally intended to support wedding expenses, provide initial capital for household establishment, and demonstrate respect toward the bride’s family, this practice frequently evolves into a transactional burden that may delay or even obstruct marriage. This article examines the Islamic legal thought of Muhammad Arsyad al-Banjari regarding balanja al-nikāḥ as articulated in his work Kitāb al-Nikāḥ. Employing library research with a normative-historical approach, the study reveals that Arsyad al-Banjari categorized balanja al-nikāḥ into three financial components: mahr as a religious obligation, and clothing and maintenance as social obligations institutionalized through the jujuran tradition. The groom’s ability to fulfill these components determines the legal status of the marriage: it is considered sunnah (recommended) if fulfilled and makrūh (reprehensible) if not. These findings indicate that Arsyad al-Banjari adopted a strategy of moderate reform by redefining jujuran as a form of gift and solidarity rather than as a prerequisite for the validity of marriage. This approach provides a model for harmonizing Islamic law and custom within the framework of legal pluralism. It offers a normative foundation for reformulating customary marriage practices in a manner that is more equitable, proportional, and consistent with the objectives of Islamic law (maqāṣid al-sharīʿah). [Praktik pemberian harta di luar kewajiban mahar dalam perkawinan adat merupakan fenomena sosio-legal yang kompleks karena tidak hanya bersifat simbolik, tetapi juga membawa implikasi langsung terhadap relasi gender, beban ekonomi keluarga, dan reproduksi hierarki sosial. Dalam masyarakat Banjar di Kalimantan Selatan, praktik ini dilembagakan melalui tradisi jujuran—penyerahan sejumlah uang dan perlengkapan pribadi calon mempelai perempuan oleh pihak laki-laki sebelum akad nikah—yang pada mulanya dimaksudkan untuk membantu biaya resepsi, menyediakan modal awal rumah tangga, serta menjadi simbol kehormatan bagi keluarga perempuan, namun dalam praktik sering berkembang menjadi beban transaksional yang berpotensi menunda bahkan menghalangi perkawinan. Artikel ini menganalisis pemikiran hukum Islam Muhammad Arsyad al-Banjari mengenai balanja al-nikāḥ dalam karyanya yang berjudul Kitāb al-Nikāḥ. Dengan menggunakan metode penelitian kepustakaan dan pendekatan normatif-historis, penelitian ini menemukan bahwa Arsyad al-Banjari mengklasifikasikan balanja al-nikāḥ ke dalam tiga komponen finansial—mahar sebagai kewajiban syariat, serta pakaian dan nafkah sebagai kewajiban sosial yang dilembagakan melalui tradisi jujuran. Kemampuan calon suami memenuhi ketiganya menentukan status hukum perkawinan: sunah bila terpenuhi dan makruh bila tidak. Temuan ini menunjukkan bahwa Arsyad al-Banjari menerapkan strategi reformasi moderat dengan menegaskan jujuran sebagai hibah dan bentuk solidaritas, bukan syarat sah akad nikah, sehingga menghadirkan model harmonisasi antara hukum Islam dan adat dalam kerangka pluralisme hukum serta memberikan dasar normatif bagi reformulasi praktik perkawinan adat yang lebih adil, proporsional, dan sejalan dengan maqāṣid al-sharīʿah.]